Growth and survival of cuttlefish (Sepia officinalis) of different ages fed crustaceans and fish. Effects of frozen and live prey - Domingues, P. (2018)
Three feeding experiments, using live mysid shrimp, grass shrimp or fish fry as prey for 1-, 30- and 60-day-old cuttlefish were conducted to determine the efficiency of each dietary source in relation to cuttlefish size and age. Additionally, a fourth experiment using fish fry and grass shrimp, but previously frozen, was also conducted. The results showed that when 1-day-old cuttlefish were fed mysids, grass shrimp or fish for 4 weeks, mysids were the best prey, but only during the first week. From this moment until the end of the experiment, the best growth rate was when cuttlefish were fed grass shrimp. Cuttlefish fed fish fry showed the poorest growth rate throughout the experiment. Similarly, cuttlefish aged 30 or 60 days fed grass shrimp or fish fry had the best growth rates when fed grass shrimp. When cuttlefish were fed live fish, survival increased with size of cuttlefish (73.3%, 91.7% and 100% for 1, 30 and 60 days cuttlefish, respectively). In the fourth experiment, using frozen diets, overall acceptance of each diet (feeding rates) was the same for fish and shrimp. However, lower growth was obtained when cuttlefish were fed fish compared to grass shrimp. This lower growth was due to a lower food conversion (28% vs. 41%). Since cephalopod paralarvae and juvenile most likely need prey rich in polyunsaturated fatty acids (PUFA), phospholipids and cholesterol, and a moderate content in neutral lipids, we have analyzed the biochemical compositions of the different prey to evaluate the influence of this factor on growth and survival.